2020
DOI: 10.1007/s11263-020-01310-5
|View full text |Cite
|
Sign up to set email alerts
|

MimicGAN: Robust Projection onto Image Manifolds with Corruption Mimicking

Abstract: In the past few years, Generative Adversarial Networks (GANs) have dramatically advanced our ability to represent and parameterize high-dimensional, non-linear image manifolds. As a result, they have been widely adopted across a variety of applications, ranging from challenging inverse problems like image completion, to problems such as anomaly detection and adversarial defense. A recurring theme in many of these applications is the notion of projecting an image observation onto the manifold that is inferred b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Approaches such as [68] and [69] rely on projecting the test image to benign dataset manifold to detect adversarial examples. The underlying assumption in these approaches is that adversarial perturbations move the test image away from the benign image manifold and the effect of adversary can be nullified by projecting the images back onto the benign manifold before classifying them.…”
Section: Unsupervised Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Approaches such as [68] and [69] rely on projecting the test image to benign dataset manifold to detect adversarial examples. The underlying assumption in these approaches is that adversarial perturbations move the test image away from the benign image manifold and the effect of adversary can be nullified by projecting the images back onto the benign manifold before classifying them.…”
Section: Unsupervised Approachesmentioning
confidence: 99%
“…For example, [68] use a sample approximation comprising a database of billions of natural images. On the other hand, [69] use a generative model trained on benign images to estimate the manifold. Given the estimated benign manifold, the projection is done by nearest neighbor search in [68] and gradient-based search in [69].…”
Section: Unsupervised Approachesmentioning
confidence: 99%
“…If successful, feeding the resulting latent vector to the generator should faithfully reconstruct the original image. While this is far from a trivial task [22][23][24], substantial progress has been made [19,22,[25][26][27]. In one of the most recent contributions [22], the authors demonstrated how their inversion method enables modifying facial attributes, interpolation, and diffusing the inner parts of one face image into the outer parts of another (Figure 4D).…”
Section: Trends In Cognitive Sciencesmentioning
confidence: 99%
“…When a pre-trained generative model is available, one can always reproject an OOD sample onto the image manifold, e.g., MimicGAN [2], to produce meaningful reconstructions. However, in this paper, we consider the setup where we assume no access to the original data (or a generative model), but only to a black-box predictive model.…”
Section: Introductionmentioning
confidence: 99%